?EFFECT OF COOKING METHOD AND LENGTH OF COOKING TIME ON NUTRITIVE VALUE OF VARIOUS BEAN BROTHS (Biological Sciences - PJSIR, 2003)
Nutritive value of various bean broths was evaluated. Black grams, chick-peas, lentil, red and white kidney beans were subjected to different cooking methods for different time periods. Cooked broth was analyzed for total solids, °Brix, protein, minerals and total soluble sugars to assess the nutritive value. Variable amounts of these nutrients were obtained in these broths depending upon the cooking method and cooking time. These nutrients in broth showed a significant increase with cooking time. Total solids and °Brix, in these bean broths varied from 8.10 - 30.00 and 5.40 - 20.00 g/l,whereas the amount of protein, minerals and soluble sugars ranged from 4.10 - 17.00, 2.20 - 5.80 and 1.20 - 4.80 g/l, respectively. However, maximum amount of nutrients in broth was obtained by pressure cooking of beans.